2009
DOI: 10.1090/s0002-9939-09-10001-1
|View full text |Cite
|
Sign up to set email alerts
|

Hopf quivers and Nichols algebras in positive characteristic

Abstract: We apply a combinatorial formula of the first author and Rosso, for products in Hopf quiver algebras, to determine the structure of Nichols algebras. We illustrate this technique by explicitly constructing new examples of Nichols algebras in positive characteristic. We further describe the corresponding Radford biproducts and some liftings of these biproducts, which are new finite dimensional pointed Hopf algebras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…Cibils and Rosso [7] (see also [8]) showed that a graded Hopf algebra structure on kQ endows Q 0 with a group and kQ 1 with a kQ 0 -Hopf bimodule structure. This in turn gives rise to what Cibils and Rosso call ramification data.…”
Section: 5mentioning
confidence: 99%
“…Cibils and Rosso [7] (see also [8]) showed that a graded Hopf algebra structure on kQ endows Q 0 with a group and kQ 1 with a kQ 0 -Hopf bimodule structure. This in turn gives rise to what Cibils and Rosso call ramification data.…”
Section: 5mentioning
confidence: 99%
“…Further classification of the algebra of the Hopf quiver and its dual version with its corresponding self-dual Hopf modules structures are given by Huang et al [14]. Cibils et al [6] obtained the structures of Nichols algebras in positive characteristic from the Hopf quiver algebras. We generalize this notion by giving a definition of the ramification data for a Clifford monoid.…”
Section: Weak Hopf Quiversmentioning
confidence: 99%
“…In [27], Scherotzke classified finitedimensional pointed rank one Hopf algebras in positive characteristic which are generated by group-like and skew-primitive elements. Many Hopf algebras in positive characteristic also come from Nichols algebras which are of much interest, see [7,15].…”
Section: Introductionmentioning
confidence: 99%